Religion in Modern Taiwan Tradition and Innovation in a Changing Society - Clart, Philip; Jones, Charles B. (University of Hawaii Press, 2003)
Religion in Modern Taiwan takes a new look at Taiwan's current religious traditions and their fortunes during the twentieth century. Beginning with the cession of Taiwan to Japan in 1895 and the currents of modernization that accompanied it, the essays move on to explore the developments that have taken place as Buddhists, Daoists, Christians, non-Han aborigines, and others have confronted, resisted, and adapted to (even thrived in) the many upheavals of the modern period. An overview of Taiwan's current religious scene is followed by a comprehensive look at the state of religion in the country prior to the end of World War II and the return of Taiwan to Chinese sovereignty. The remaining essays probe aspects of change within individual religious traditions. The final chapter analyzes changes that took place in the scholarly study and interpretation of religion in Taiwan during the course of the twentieth century. Religion in Modern Taiwan will be read with interest by students and scholars of Chinese religion, religion in Taiwan, the modern history of Taiwan, and by those concerned with issues of religion and modernization. Contributors: Chang Hsun, Philip Clart, Shiun-wey Huang, Christian Jochim, Charles B. Jones, Paul Katz, André Laliberté, Lee Fong-mao, Randall Nadeau, Julian Pas, Barbara Reed, Murray A. Rubinstein